KOMBINASI PRELOADING DAN PENGGUNAAN PRE-FABRICATED VERTICAL DRAINS UNTUK MEMPERCEPAT KONSOLIDASI TANAH LEMPUNG LUNAK (STUDI KASUS TANAH LEMPUNG SUWUNG KANGIN) - Hidayati, Anissa Maria; Wirya Ardana, Made Dodiek (Jurnal Ilmiah Teknik Sipil, 2012)
In general, soil on mangrove forest formed from deposit of clay, silt and organic matter with high water content. The soil is impermeable with very high compressibility potential and provide low bearing capacity. Due to these soil cha-racteristics, the soil tends to experience a large value of settlement. A combination of preloading method and pre-fabricated vertical drains (PVD) installation is an improvement method to exceed the soil consolidation process. A series of pre-loading load are applied on a soil layerin order to produce stress to trigger the soil consolidation preocess. Whilst, the insertion of PVD is aimed to shorten the drainage path for the drained water from the soil body to the respective surface. The objective of the study is to determine the conventional consolidation time and it’s comparison to the consolidation time obtained from teh combination of preloading and PVD in the same degree of primary consolidation. The study results on soft clay soil on Suwung Kangin resort show a valueable result to speed up the time of primary consolidation process. In addition, the combination of preloading and pre-fabricated vertical drains demonstrate an improvement in soil bearing capacity. A equilateral trianggular PVD insertion pattern with 1 m in spacing to a depth of 16 m in soft clay soil layer are able to speed up the primary consolidation time of 7276.84% on the design load. Slope stability analysis to circular failure on preloading embankment show a value of factor safety greater than 1.
Keywords: preloading, pre-fabricated vertical drain, waktu konsolidasi